Peran Konformitas Terhadap Perilaku Merokok Remaja - Wardhani, Ni luh Sekar Kusuma (Widya Cakra: Journal of Psychology and Humanities; Vol 1 No 1 (2020): Volume 1 Nomor 1 Tahun 2020 - Widya CakraDO - 10.24843/widyacakra.2020.v1.i1.p69190, 2020)
Smoking behavior is not a taboo to be heard. Nowadays cigarettes are consumed in various ages. Smoking behavior is the activity of burning cigarettes and then smoking it, then the smoke will be exited so that the people around him can breathe in the blowing smoke. Hazardous chemicals in cigarettes do not also make people stay away from smoking behavior. Smokers in the world specifically in Indonesia continues to increase. In several studies found that adolescents are the population that consumes the most cigarettes. Various factors are the reasons teenagers make smoking their choice. Peers as one of the factors that contribute to the presence of conformity in adolescent’s lives, contributes to the emergence of smoking behavior in adolescents. Understanding the meaning of conformity in the emergence of teenage smoking behavior is very important at this time to know what causes smoking behavior in adolescents to emerge and can survive.